New synthesis of oligosaccharides modelling the M epitope of the Brucella O-polysaccharide - Tsvetkov, Yury E.; Volkov, Timur M.; Eremin, Sergei A.; Sklyarov, Oleg D.; Kulakov, Yuri K.; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Chemistry, 2024)
Brucellosis is a dangerous zoonotic disease caused by bacteria of the genus Brucella. Diagnosis of brucellosis is based on the detection in animal and human sera of antibodies to the O-polysaccharide of Brucella lipopolysaccharide. The currently employed serodiagnosis of brucellosis relies on the use of the Brucella O-polysaccharide as a diagnostic antigen. However, the existence of bacterial species, which also express O-polysaccharides structurally similar to that of Brucella, may decrease the specificity of the brucellosis detection due to false-positive test results. It has been shown that the efficiency of the test can be significantly improved by using synthetic oligosaccharides that correspond to the so-called M epitope of the Brucella O-antigen. This epitope is characterized by an α-(1→3)-linkage between d-perosamine units and is unique to Brucella. Here we report on an efficient approach to the synthesis of oligosaccharides that model the M epitope of the Brucella O-polysaccharide. The approach is based on the use of the α-(1→3)-linked disaccharide thioglycoside as the key donor block. Its application allowed the straightforward assembly of a set of four protected oligosaccharides, which includes a disaccharide, two trisaccharides, and a tetrasaccharide, in five glycosylation steps. The synthesized oligosaccharides are planned to be used in the development of diagnostic tools for identifying brucellosis in humans and domestic animals, as well as a potential vaccine against it.